Tradisi Murajaah Surat Al-Baqarah dan Juz 'Amma di SMPTQ dan SMATQ Hasmi Bogor - Arifin; Muslim (Dirosah Islamiyah, 2026)
This study aims to examine the tradition of the murajaah (memorization review) curriculum for Surah Al-Baqarah and Juz ‘Amma at SMPTQ and SMATQ Hasmi, Bogor. The program is backed by the necessity of preserving Al-Qur'an memorization from the inherent human trait of forgetfulness. This policy strategically integrates Surah Al-Baqarah as a macro foundation to build students' mental endurance, alongside Juz ‘Amma as a tactical solution to support practical daily worship. The research method employed is a descriptive case study with a qualitative approach. Data were gathered through participatory observation, literature review, and in-depth interviews with curriculum staff, educators, and students. The results indicate that the murajaah activity is conducted every Monday to Saturday from 08:00 to 08:30 WIB in the auditorium using a classical method, followed by independent recitations (tasmi') in the classroom. The target management is mathematically set at 4 pages per day to minimize student burnout. This tradition is proven to yield comprehensive impacts, including achieving peace of mind, enhancing discipline, improving fluency in prayer recitations, and sharpening brain function to train students' focus and concentration in school.